Basaloid follicular hamartomas in pediatric Basal Cell Nevus Syndrome: A diagnostic challenge. Issue 7 (21st May 2021) - Besagni, Francesca; Dika, Emi; Ricci, Costantino; Misciali, Cosimo; Veronesi, Giulia; Corti, Barbara; Gurioli, Carlotta; Neri, Iria
Abstract: Basal Cell Nevus Syndrome (BCNS) is an autosomal dominant inherited disease caused by PTCH1 (9q22.3‐q31) germline mutations. Skin manifestations are mainly characterized by hyperkeratosis of the palms and soles, palmoplantar pits and a strong predisposition to develop multiple basal cell carcinomas (BCCs). Recently, it has been hypothesized that basaloid follicular hamartomas (BFH) could be included in BCNS skin features. We present three pediatric cases of GS with BCCs and BFHs. Clinical, dermoscopic and immunohistochemical tools are reported.